COMMUNICATION AND WORKING DISCIPLINE RELATIONSHIPS PERFORMANCE OF STATE CIVIL SERVANTS (ASN) IN OFFICES GOVERNMENT OF KECAMATAN SIBABANGUN CENTRAL TAPANULI DISTRICT - Fauziah Nur Simamora; Kaharuddin Kaharuddin (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
: The research objective is to determine whether there is a relationship between communication and work discipline together with the performance of employees at the Sibabangun District Government Office, Tapanuli Tengah Regency. The author provides a temporary answer to this study are: There is a relationship between communication and work discipline with employee performance at the office of the Sibabangun subdistrict, Tapanuli Tengah regency. The research population of all State Civil Servants (ASN) at the Government Office of the Sibabangun District, Central Tapanuli Regency was 37 people and sampled. Based on the results of simultaneous testing, it was obtained that the Fcount value (46.753) was greater than Ftable (3.25) or (46.753> 3, 25) and Sig.á (0.000a) is less than alpha 5% (0.05). This indicates that the results of the study reject H0 and accept Ha. Thus the variables of communication and work discipline simultaneously have a relationship with performance. The partial test results are: 1). The value of tcount ? t table is (2.642 ? 2.026) and Sig-t ? 0.05 is (0.012 ? 0.05). 2) The value of t count ? t table, namely (4.158 ? 2.026) and Sig-t ? 0.05, which is equal to (0.00 ? 0.05) meaning that there is a positive relationship between the independent variable and the dependent variable. Based on the multiple linear regression model obtained, the regression equation Y = -4.402 + 0.450 X1 + 0.686 X2. Shows that there is a relationship between communication and work discipline with performance. It is suggested that communication between employees needs to be improved so that each task is carried out and the goals to be achieved can be achieved. Employee discipline enforcement should be done more firmly and with direction, this is very important to increase the responsibility of all employees, so that employee performance will increase